2022
DOI: 10.1002/jad.12047
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' expectancy–value profiles in school context: The impact of self‐directed learning intervals

Abstract: Introduction Using the situated expectancy–value theory, it becomes possible to explain motivational functioning across alternating learning conditions not only at a particular moment but also over time. The situated expectancy–value theory provides evidence for the critical role of context. The present research examines how adolescents' success expectancies, task values, and effort develop when the conditions of the academic environment change. It also evaluates whether adolescents adopt more adaptive expecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The purpose of developing personas in this context is to create descriptions of prototypical mathematics students, to help empathise with prototypical mathematics students in the design processes of digital mathematics learning resources, and to provide a new student-centred research approach in mathematics education research. While this new approach to mathematics education research represents an important addition to the field, it should be considered a supplement to existing research frameworks such as learners’ goal orientations [ 27 ] and person-oriented approaches that aim to cluster students according to specific characteristics [ 19 ].…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of developing personas in this context is to create descriptions of prototypical mathematics students, to help empathise with prototypical mathematics students in the design processes of digital mathematics learning resources, and to provide a new student-centred research approach in mathematics education research. While this new approach to mathematics education research represents an important addition to the field, it should be considered a supplement to existing research frameworks such as learners’ goal orientations [ 27 ] and person-oriented approaches that aim to cluster students according to specific characteristics [ 19 ].…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…Research based on psychological measures of student characteristics shows that it can be difficult to translate research findings into actual school practices. Our aim is that the personas developed in this project contribute to research by reflecting typical patterns of characteristics of mathematics learners which serve as a supplement to other available characterisations of students that are based on approaches from educational psychology such as motivational profiles of school students [ 19 ] or clusters of STEM students based on motivational trajectories [ 20 ]. We intend that the personas can bridge findings from research with design processes in practice and be of practical use for developers of digital resources for teaching and learning mathematics as well as for teachers in lesson design.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SEVT has shown that beliefs are context-sensitive and interact over short periods of time [51]. As seen above, using SEVT, it is possible to explain the motivational functions of alternate learning conditions not only at specific moments but also over time [52]. The COVID-19 pandemic is a special situation that will affect people's perceptions and value judgments.…”
Section: Research Modelmentioning
confidence: 99%
“…To be a self-directed learner was then identified as having the ability to learn independently (Knowles 1975) and was found to be commonly associated with adult education (Knowles 1978;Loeng 2018). What was also discovered is that, for self-directed learning to be effective, it requires self-initiation based on the motivations and values of the individual, rather than those imposed by society (Loeng 2018;Nash 2020;Schweder and Raufelder 2022). Consequently, self-direction was recognized as the cornerstone of democracy (Loeng 2020) and discovered to be the aim of adults and associated with improved health when undertaken (Beller 2021).…”
Section: Introductionmentioning
confidence: 99%